PREPARATION OF MgO-CeO2 MIXED OXIDE WITH IONIC LIQUID AS CATALYST FOR DIMETHYL CARBONATE SYNTHESIS VIA TRANSESTERIFICATION - Haznan Abimanyu; Kye Sang Yoo; Byoung-Sung Ahn (Jurnal Kimia Terapan Indonesia, 2010)
The synthesis and application of dimethyl carbonate (DMC) are achieving increasing importance due to its low toxicity and versatile reactivity. The phosgenation-route has been losing attraction recently due to the use of virulent phosgene. In transesterification process, DMC is co-generated with ethylene glycol (EG). In this study, various ionic liquids were used as template in coprecipitation methods to prepare mesoporous MgO-CeO2 mixed oxides particles. Among the ionic liquids, [Bmim][BF6] displayed the best performance in terms of activity, while [Omim][PF6] obtained the best selectivity for this reaction. The addition of IL's in the coprecipitation method increased the surface areaand pore volume of the catalysts. Meanwhile, the crystallite size of the catalysts was reduced many times. However, there is no effect of the surface areaand particle size as well on the catalytic activity of the catalyst in this reaction. The activity and selectivity of the catalyst depend on the base strength distribution. The moderate basic site is responsible for the catalytic activity, while the selectivity is more dependableon the strong basic site. Keyword: preparation, MgO-CeO2, ionic liquid, dimethyl carbonate, coprecipitati